Preventive effects of hesperidin on diabetic nephropathy induced by streptozotocin via modulating TGF-β1 and oxidative DNA damage. (2nd October 2018) - Kandemir, Fatih Mehmet; Ozkaraca, Mustafa; Küçükler, Sefa; Caglayan, Cuneyt; Hanedan, Basak
Abstract: Hesperidin (HSP) is a natural bioflavonoid with active pharmacological properties. This study was conducted to investigate the hypoglycemic and antioxidant effects of HSP on streptozotocin-induced diabetic nephropathy in rats. Serum urea, creatinine and malondialdehyde levels increased in the diabetic group, while antioxidant enzyme activities decreased compared to the control group. Moreover, transforming growth factor-beta 1 level, 8-hydroxy-2′-deoxyguanosine expression and histopathological changes in renal tissue were increased in the diabetic group. On the other hand, HSP therapy significantly regulated these values in diabetic rats. Our results indicated that HSP might be helpful to protect diabetic nephropathy.